2019
DOI: 10.1089/aut.2018.0028
|View full text |Cite
|
Sign up to set email alerts
|

Friends and Lovers: The Relationships of Autistic and Neurotypical Women

Abstract: Background: Little is known about the friendships and relationships of autistic adults, despite decades of research evidence showing the benefits of close relationships for neurotypical adults. Even less is known about the relationships of autistic women, or how their relationships compare to those of neurotypical women. This mixed-methods study therefore examined differences in the social relationships of autistic women in relation to their neurotypical counterparts. Methods: Thirty-eight women (19 autistic w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…Fifth, all measures in this study were self-report, and therefore other metrics including reports of caregivers, clinician interviews, and qualitative data would be beneficial to explore these processes from multiple informants and perspectives. Qualitative exploration, in particular, of social contact, loneliness, and quality of relationships would provide richer information about the lived experiences of autistic adults (for instance, see Sedgewick et al, 2019). Finally, a range of factors not measured here should continue to be considered in future research on pathways between autism features and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, all measures in this study were self-report, and therefore other metrics including reports of caregivers, clinician interviews, and qualitative data would be beneficial to explore these processes from multiple informants and perspectives. Qualitative exploration, in particular, of social contact, loneliness, and quality of relationships would provide richer information about the lived experiences of autistic adults (for instance, see Sedgewick et al, 2019). Finally, a range of factors not measured here should continue to be considered in future research on pathways between autism features and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Although some recent research has qualitatively explored autistic people’s friendships from their own perspective (e.g. Sedgewick, Crane et al, 2019 ; Sedgewick, Hill & Pellicano, 2019 ), little is known about whether autistic people experience self-reported differences in relationships with autistic and non-autistic people.…”
Section: Introductionmentioning
confidence: 99%
“…Despite differences in social interaction, autistic people do not necessarily differ from their neurotypical peers in their desire for social relationships (Bauminger & Kasari, 2000; Cresswell et al, 2019). Many autistic people are motivated to have friendships and sustain meaningful and lasting social relationships (Bargiela et al, 2016; Daniel & Billingsley, 2010; Sedgewick, Crane, Hill, & Pellicano, 2019; Sinclair, 2010). However, initiating, maintaining and navigating these relationships may be difficult for autistic people, due to differences in autistic social cognition.…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties developing and maintaining relationships are core diagnostic criteria for autism. Sedgewick et al (2019) explored the relationships of autistic women, reporting they found it harder to interpret social situations, had fewer and more intense relationships and more difficulties within their relationships than non-autistic women. Autistic women reported that their negative experiences in interpersonal situations were largely related to their difficulties with social inference.…”
Section: Social Communication and Social Interactionmentioning
confidence: 99%
“…Parents reported improvements in their daughters' relationships over time, which they attributed to maturing of social skills with age (Sedgewick et al, 2018). Autistic women also report feeling happier in their relationships and more confident in their social skills as they progressed into adulthood (Sedgewick et al, 2019). Kock et al (2019) explored the intimate relationship experiences of autistic women.…”
Section: Social Communication and Social Interactionmentioning
confidence: 99%